Design and rationale of FOCUS (PX-171-011): a randomized, open-label, phase 3 study of carfilzomib versus best supportive care regimen in patients with relapsed and refractory multiple myeloma (R/R MM) - Hájek, Roman; Bryce, Richard; Ro, Sunhee; Klencke, Barbara; Ludwig, Heinz (BMC cancer, 2012)
BACKGROUND: Carfilzomib is a next-generation proteasome inhibitor with single-agent activity in patients with relapsed and refractory multiple myeloma (R/R MM). In PX-171-003-A1, a single-arm phase 2 study of carfilzomib monotherapy in heavily pretreated patients, the overall response rate was 23.7%, 37% of patients achieved ≥ minimal response and median overall survival (OS) was 15.6 months. Based on this study, carfilzomib was recently approved by the US Food and Drug Administration for the treatment of R/R MM. Herein we describe the trial design and rationale for a phase 3 randomized study, FOCUS (CarFilzOmib for AdvanCed Refractory MUltiple Myeloma European Study), being conducted to compare OS after treatment with single-agent carfilzomib to best supportive care (BSC) regimen in R/R MM. METHODS: Patients must have received ≥3 prior regimens, must be responsive to at least 1 line of therapy, and be refractory to their most recent therapy. Eligible patients are randomized 1:1 to receive either carfilzomib (28-day cycles at 20 mg/m(2) IV on Days 1-2 of Cycle 1, escalating to 27 mg/m(2) IV on Days 8, 9, 15, and 16 and continuing at 27 mg/m(2) through Cycle 9 and Days 1, 2, 15, and 16 ≥ Cycle 10) or an active BSC regimen (corticosteroid treatment of prednisolone 30 mg, dexamethasone 6 mg, or equivalent every other day with optional cyclophosphamide 50 mg PO once daily). Patients will continue treatment until disease progression, unacceptable toxicity, or treatment discontinuation and will then enter long-term follow-up for survival. The primary endpoint is OS and secondary endpoints include progression-free survival, overall response rate, and safety. Disease assessments will be determined according to the International Myeloma Working Group Uniform Response Criteria with minimal response per European Blood and Marrow Transplantation Group criteria. CONCLUSIONS: This phase 3 trial will provide more rigorous data for carfilzomib, as this is the first carfilzomib study with OS as the primary endpoint and will not be confounded by crossover and will provide more robust secondary response and safety results that will add to the data set from prior phase 2 studies. FOCUS will facilitate regulatory approvals around the world and expand treatment options for patients with R/R MM. TRIAL REGISTRATION: EudraCT No. 2009-016840-38; NCT01302392.
Keywords: Clinical Protocols; klinické protokoly; mnohočetný myelom; oligopeptidy; protinádorové látky; Oligopeptides; Humans; Multiple Myeloma; Recurrence; recidiva; Antineoplastic Agents; výzkumný projekt; Research Design; lidé